Extraction of proteins from two marine macroalgae, Ulva sp. and Gracilaria sp., for food application, and evaluating digestibility, amino acid composition and antioxidant properties of the protein concentrates. (February 2019) - Kazir, Meital; Abuhassira, Yarden; Robin, Arthur; Nahor, Omri; Luo, Jincheng; Israel, Alvaro; Golberg, Alexander; Livney, Yoav D.
Abstract: With rising global population and decreasing available land and fresh water resources, the oceans provide an attractive domain for sourcing nutrients. The marine macroalgae Ulva sp. and Gracilaria sp. are candidate raw biomass. Ulva sp. has high growth rate and Gracilaria sp. has high protein content and their seasonal growth is complementary, allowing almost year-round high yield protein production. In this study, we aimed at developing an effective process, to yield a high macroalgae protein content concentrate suitable for food application, and studying the digestibility, amino acid composition and antioxidant properties of the obtained algal protein concentrates (APCs). We developed a new protein extraction protocol, and compared it to several published protocols. The developed protocol is food-grade, and yielded APC from Ulva and form Gracilaria, containing 70 and 86% protein respectively. The amino acid compositions of the APCs suggest their possible use as sources of essential amino acids. Simulated gastro-intestinal digestion showed that APCs proteolysis of at least 89% can be reached. We found that the APCs exhibit antioxidant activity, which is similar to that of known protein isolates in the hydrogen atom transfer mechanism, but 10 to 20 times higher in the single electron transfer mechanism. These results suggest that polyphenolic compounds might be still present in the APCs and contribute to their antioxidant activity. Our results suggest that the protein concentrates extracted from Ulva sp. and Gracilaria sp. seem to be promising sustainable sources for human nutrition thanks to their essential amino acids content, digestibility and antioxidant properties. Graphical abstract: Image 1 Highlights: Macroalgae – a new and renewable source for extracted nutrients. Food grade extraction yielded high purity protein powders. Extracted proteins contain good levels of essential amino acids. Protein concentrates exhibit high antioxidant activity. Extracted proteins were ∼90% digestible under simulated gastro-intestinal conditions.